Prediction of Epitopes in the Proteome of Helicobacter pylori (2018)
Helicobacter pylori (H. pylori) is classified by the World Health Organization (WHO) as a group I carcinogen and is one of the most efficient human pathogens with over half of the world's population colonized by this gram-negative spiral bacterium. H. p